2012
DOI: 10.1016/j.jpainsymman.2011.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Education in Advanced Disease

Abstract: Health professionals identify and acknowledge a range of factors that influence their ability to deliver education to patients with advanced disease. The types of circumstantial factors identified in this review can influence the successful delivery of educational interventions and need to be considered when such interventions are being developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…A key finding from studies in this field is that education for self-management of cancer pain should be integrated into routine practice [29,19,30]. Despite optimism that this can be achieved 'without undue extra resources or time' [14, p393] there are numerous factors, often presented as barriers, which influence the implementation of patient education for selfmanagement -including health professionals' knowledge, attitudes and beliefs [26,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A key finding from studies in this field is that education for self-management of cancer pain should be integrated into routine practice [29,19,30]. Despite optimism that this can be achieved 'without undue extra resources or time' [14, p393] there are numerous factors, often presented as barriers, which influence the implementation of patient education for selfmanagement -including health professionals' knowledge, attitudes and beliefs [26,30].…”
Section: Discussionmentioning
confidence: 99%
“…For example, research has shown that 'self-action strategies' to manage the effects of advanced cancer on appetite and eating can lead to changes in patients' thinking and behaviour which enhance well-being [17]; the importance of recognizing and supporting patients' selfmanagement strategies in regard to medicines taking when their life expectancy is reduced by advanced cancer has been demonstrated; and, importantly, self-management has been shown to fluctuate during the trajectory of an illness, with advancing metastatic disease and/or feeling more ill prompting changes in how actively individuals self-manage [19]. Supporting self-management has become a standard approach for health care professionals working with people who experience chronic non-cancer pain [21,22] and many studies and reviews have reported that patient-focused educational interventions, including self-management, can also improve pain control in patients with advanced cancer [23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…The review examining health professionals' views of delivering education to patients with advanced disease discovered three key themes that related to health professionals' capacity to deliver education and aid decision-making; the context in which education is delivered, and the timing and triggers that initiate education (Flemming et al, 2012). There was a perception that continuing professional development, both clinically specific and in educational techniques, enhances health professionals' confidence and skill, which then improves capacity to deliver education.…”
Section: Preliminary Findings From the Qualitative Evidence Synthesesmentioning
confidence: 99%
“…Five of the reviews made recommendations regarding the way an educational intervention may be formatted and delivered, including information about the triggers for when it might be delivered (Bennett et al, 2009;Cummings et al, 2011;Flemming et al, 2012;Gorin et al, 2012;Koller et al, 2012). Through the qualitative evidence syntheses, it was identified that common triggers for the initiation of an educational intervention arise from routine assessment and monitoring of patients.…”
Section: Delivery Of Education: Its Triggers and Formatmentioning
confidence: 99%
See 1 more Smart Citation